Research on job insecurity and well‐being in the workplace from triple perspectives of HRM, leader and coworker. (2nd June 2022) - Li, Xiufeng; Lin, Congcong; Dong, Yiting
Abstract : This research aims to investigate how organizational high‐commitment HRM, leader's trust, and coworker support influence well‐being in the workplace. Based on signaling theory and conservation of resources theory, we first posit that high‐commitment HRM is positively related to work well‐being through reducing job insecurity. We also assume that leader's trust in subordinates and coworker support serve as important moderators in this relationship. We adopt a multilevel, multisource field survey with 1369 supervisors and 6975 employees from 128 firms in China. Results support our hypotheses, indicating that job insecurity mediates the relationship between high‐commitment HRM and work well‐being. Leader's trust in subordinates and coworker support moderate the mediating effect of job insecurity; specifically, the effect of job insecurity is stronger when leader's trust is high rather than low, and when coworker support is low rather than high. These findings provide a finer‐grained understanding of how organizational HRM, leaders, and coworkers interact to affect employee job insecurity and, finally, work well‐being.